Effective Coverage of Emergency Obstetric and Newborn Care Services in Africa: A Scoping Review - Alemayehu M; Yakob B; Khuzwayo N (Open Access Emergency Medicine, 2023)
Mihiretu Alemayehu,1,2 Bereket Yakob,1,3 Nelisiwe Khuzwayo2 1School of Public Health, College of Health Sciences and Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2School of Nursing and Public Health, Discipline of Public Health, University of Kwazulu-Natal, Durban, South Africa; 3School of Population and Public Health, the University of British Columbia, Vancouver, BC, CanadaCorrespondence: Mihiretu Alemayehu, PO Box: 138, Wolaita Sodo, Ethiopia, Tel +251913213443, Fax +251465515113, Email mihiretua@gmail.comObjective: This scoping review aimed to map the evidence of effective coverage (EC) of EmONC (Emergency Obstetric and Neonatal Care) services and associated factors in Africa.Methodology: The review used PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews) checklist to select, appraise, and report the findings. We searched four databases (PubMed, Web of Science, Google Scholar, and Scopus) and grey literature published between Jan 01, 2011 – Dec 31, 2020. The search terms included “emergency”, “obstetric”, “newborn”, “effective coverage”, and “quality” with Boolean terms, AND and OR. The review was conducted using title, abstract, and full-article screenings. The results were analyzed thematically using NVivo v12 qualitative research data analysis software.Results: Of the 1811 searched studies, 32 met the eligibility criteria for review. The majority of the studies were from East (56.3%) and Western (28.1%) Africa. Most studies were cross-sectional, had targeted health facilities, and combined two or more data collection techniques. The thematic analysis yielded three themes: EmONC service utilization, quality of EmONC service, and factors associated with the quality of EmONC services. The review showed a scarcity of evidence and variations regarding the crude coverage, quality of care, and factors affecting the quality of EmONC services in Africa.Conclusion: The review reported that the utilization of EmONC services was below the WHO-recommended 100% in all studies, though some reported improvements over time. Disparities in EmONC services quality were paramount across studies and contexts. However, the methodological and analytical incongruity across studies brought difficulties in tracing and comparing the progress made in EmONC services utilizations.Registration: This scoping review protocol was first registered on the Open Science Framework (OSF) on Aug 27, 2021 (https://osf.io/khcte/).Keywords: maternal health, newborn health, obstetric care, perinatal care, emergency medicine